Ulcerative colitis: current pharmacotherapy and future directions. (August 2014) - Bezzio, Cristina; Furfaro, Federica; de Franchis, Roberto; Maconi, Giovanni; Asthana, Anil Kumar; Ardizzone, Sandro
<x xml:space="preserve">Abstract</x> Introduction: Ulcerative colitis (UC) is a chronic relapsing disease, characterised by alternating of acute and remission phases. Although the aetiology is unknown, in recent years, there has progressively been greater knowledge of the various pathogenetic mechanisms underlying the disease itself. Thus, from therapy based on generically anti-inflammatory or immunosuppressive agents, treatment is gradually moving towards drugs that selectively block specific inflammatory mediators, such as TNF-α. Areas covered: This review provides the most significant data about the therapeutic role of different drugs currently available for the treatment of UC. In addition, the critical therapeutic areas on which research could focus in the near future are discussed. Expert opinion: UC is a disease affecting young patients, whose quality of life may be strongly compromised by the progression of disease. Over time, the disease may lead to an impairment of the normal anatomy and physiology of the colon, and the cumulative incidence of dysplasia and colorectal cancer increases with the time. Thus, the main aims of the near future should be both a better definition of patients at risk for a poor clinical course and progression of disease, and the development of a much more aggressive treatment for patients with a poor prognosis.